Analisis Disparitas Pendapatan dan Pertumbuhan Ekonomi Kabupaten/Kota di Provinsi Bali - Ni Kadek Sri Wahyuni; Ida Bagus Putu Purbadharmaja (Universitas Veteran Bangun Nusantara, 2024)
The purpose of this study is to find out the factors that can affect economic growth and income disparity of districts/cities in Bali Province. The data used in this study is secondary data obtained from the Badan Pusat Statistik (BPS) of Bali Province. The method of data collection is a non-participant observation method with a total of 90 observations starting from 2013-2022. The analysis technique used is the path analysis technique. The results of the study show that (1) Directly investment has a positive and insignificant effect, minimum wage has a negative and significant effect, and government expenditure has a positive and significant effect on the economic growth of districts/cities in Bali Province. (2) Directly investment has a positive and insignificant effect, minimum wage has a negative and significant effect, government expenditure and economic growth have a negative and insignificant effect on the income disparity of districts/cities in Bali Province. (3) Indirectly, investment, minimum wage, and government expenditure have no effect on income disparity through economic growth of districts/cities in Bali Province.